Accelerating growth and job creation in South Asia - SAARC Business Conclave 2007 : Mumbai, India); Ghani, Ejaz.; Ahmed, Sadiq; South Asian Association for Regional Cooperation; World Bank. South Asia Regional Office (New Delhi ; New York : Oxford University Press, 2009)
Transcript of papers presented during the 2nd SAARC Business Conclave held in Mumbai, India, in 2007 organized by South Asia Region of the World Bank in collaboration with South Asian Association for Regional Cooperation.
Includes statistics.
Includes bibliographical references.
Keywords: Economic development -- South Asia -- Congresses; Economic development -- South Asia -- Statistics -- Congresses; Job creation -- South Asia -- Congresses; Job creation -- South Asia -- Statistics -- Congresses; Manpower policy -- South Asia -- Congresses; Manpower policy -- South Asia -- Statistics -- Congresses; South Asian cooperation -- Congresses